Operational risk analysis with approach enterprise risk management - Dewi Cahyani Pangestuti; Heni Nastiti; Renny Husniati (AKUNTABEL, 2022)
The more risk management is used in a company, the more it will increase the value of the company and also affect how much money the company makes. Risk management, carried out by company managers, is the company's way of anticipating the risks that occur. The purpose of this study is to recognize, identify, assess, and control operational risks of PT. Indosat Ooredoo Tbk. in the Network Operation Center division. The research method used is risk analysis with Enterprise Risk Management. The conclusions in this study are that 49 risks have been identified, including 10 risks that include acceptable or acceptable risk criteria, 32 risks that include supplementary issue risk criteria or risks that require action if the company's resources are available, and 7 risks that include risk issues or risk criteria that immediately need to be managed and reduced. Operational risks to PT. Indosat Ooredoo, like the risk of thuggery in the Regional Operation department, have a big effect and are likely to happen. Meanwhile, the risk is the least in the Partner Management department.